(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The word retrofit means to apply new technologies to an older system. Retrofit is process by adding some new features that were not there before. Retrofitting in construction industry refers to re-strengthening of existing structure to make them seismic resistant. Retrofitting is a technique to improve the structural capacities including the strength, stiffness, ductility, stability of a building that is found to be deficient. In rural side of Pune, most of the residential buildings have been designed only for dead and live loads. Since Pune lies in zone III, the buildings located in this zone needs to be seismic resistant. Seismic retrofitting is necessary in case of any damages in high seismic prone area. The main objective of this thesis is to study various methods used for rehabilitation repairs and retrofitting in construction industry that includes new construction techniques and traditional construction techniques, to minimize retrofitting costs and waste without affecting production quality and to minimize environmental effects.This study includes visual inspection and advance technique to rehabilitation repairs and retrofitting survey in which we can find out the factor affecting the repair cost which directly related with material use in retrofitting. The factors affecting the retrofitting cost and time were identified through the literature based on previous research. The comparison of time for both material used in retrofitting work in each material showed that the material which includes advanced method, new techniques, installation process is the most suitable alternative to the existing traditional method like cement slurry.